Enhancing learner autonomy in teamwork skills: Strategies of Vietnamese tertiary EFL teachers in a changing educational landscape - Hieu, Hua Hong; Thao, Le Thanh (Nurture, 2024)
Purpose: This study explores the strategies used by Vietnamese tertiary English as a Foreign Language (EFL) teachers to promote learner autonomy in teamwork skills, crucial in the evolving context of language education in Vietnam. Design/Methodology/Approach: Employing semi-structured interviews, the research involved nine EFL teachers from two Vietnamese educational institutions, representing various career stages: novice, mid-career, and near-end career. Findings: Analysis through thematic frameworks revealed that teachers utilize diverse methods like collaborative learning projects, reflective practices, technology-enhanced learning, and real-world tasks. These strategies, adaptable to the Vietnamese cultural and educational context, proved effective across different teaching stages. Conclusion: The findings underscore the importance of contextually adapted teaching strategies, the increasing role of technology in EFL education, and the value of experiential learning. It demonstrates how Vietnamese EFL teachers’ approaches can significantly impact learner autonomy in teamwork skills. This research contributes to the literature by providing insights into effective EFL teaching strategies within non-native English-speaking environments, offering valuable perspectives for educators, curriculum designers, and policymakers. Research Limitations: The study identifies limitations, including a small sample size and reliance on qualitative data, suggesting the need for broader research with diverse methodologies. Practical Implications: This research emphasizes the necessity for culturally adapted teaching strategies and technological integration in EFL education to enhance learner engagement. Contribution to Literature: The study emphasizes the efficacy of context-specific tactics in enhancing learners' abilities, providing significant perspectives for educators and policymakers on enhancing EFL teaching practices through experiential learning and digital resources.